Can Physical Exercise Help Deal With the COVID-19 Stressors? Comparing Somatic and Psychological Responses - Qian, Junwei; Tong, Jiajin; Xu, Ruiheng (Frontiers in Psychology, 2022)
This research aims to explore whether physical exercise can buffer the impact of the COVID-19 stressors. Based on the cross-stressor adaptation hypothesis, we proposed a moderated mediation model relating the COVID-19 stressors to sleep disorder via somatic and worry complaints, depending on the amount of physical exercise. A sample of working adults in Beijing (N = 207) filled surveys in two waves during the COVID-19 pandemic. Structural regression analysis showed that physical exercise moderates the impact of the COVID-19 stressors on sleep disorder via somatic complaints (index = −.11, 95% CI [−.22, −.01]), rather than psychological worry complaints (index = −.01, 95% CI [−.07, .04]). Specifically, the COVID-19 stressors increase somatic complaints for people with a low amount of physical exercise (b=.17, p=.01]), while the COVID-19 stressors are not significantly related to somatic complaints for people with a high amount of physical exercise (b=−.06, p=.33). This research extends the cross-stressor adaptation hypothesis and provides evidence on an individual intervention of physical exercise to deal with the COVID-19 pandemic.